Analisis Keterampilan Technological Pedagogical Content Knowledge (TPACK) Pada Calon Guru Matematika Sumatera Barat - Iltavia; Diana, Siti Noor (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
The background to this research is the emergence of the Independent Curriculum which requires teachers to be able to implement TPACK in the learning process. Based on classroom experience, education students as prospective teachers are able to use technology, but are not yet accustomed to implementing TPACK in learning. The aim of this research is to analyze the level of TPACK ability in prospective mathematics teachers in West Sumatra. The research method used in this research is descriptive quantitative with a correlational approach. The research location for this activity is the mathematics education study program in the West Sumatra area. The population in this study were all students of the Mathematics Education Study Program spread across the West Sumatra campus. The data collection tool used in this research was a student questionnaire to observe TPACK abilities. The research results in the form of Technological Pedagogical Knowledge, Technological Content Knowledge, and Technological Pedagogical Content Knowledge have lower values, with the highest value being Technological Pedagogical Knowledge ( 81.38) and lowest on Technological Pedagogical Content Knowledge (74.31). This shows that the integration of these three domains (technology, pedagogy, and content) requires more attention to improve understanding and skills. The conclusion of this research is that the average percentage of qualitative criteria for TPACK skills = 81.38 with very good criteria.   Latar belakang penelitian ini adalah munculnya Kurikulum Merdeka yang menuntut guru untuk mampu mengimplementasikan TPACK dalam proses pembelajaran. Berdasarkan pengalaman di kelas, mahasiswa Pendidikan sebagai calon guru mampu untuk menggunakan teknologi, tapi belum terbiasa mengimplemensikan TPACK dalam pembelajaran. Tujuan penelitian ini adalah untuk menganalisis tingkat kemampuan TPACK pada calon guru matematika di Sumatera Barat. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan pendekatan korelasional. Tempat penelitian dalam kegiatan ini adalah program studi pendidikan matematika yang ada di daerah Sumatera Barat. Populasi dalam penelitian ini adalah seluruh mahasiswa Program Studi Pendidikan Matematika yang tersebar di kampus Sumatera Barat. Alat pengumpul data yang digunakan dalam penelitian ini adalah lembar angket mahasiswa untuk mengamati kemampuan TPACK. Hasil penelitian berupa Pengetahuan Teknologi-Pedagogi (Technological Pedagogical Knowledge), Pengetahuan Teknologi-Konten (Technological Content Knowledge), dan Pengetahuan Teknologi-Pedagogi-Konten (Technological Pedagogical Content Knowledge) memiliki nilai yang lebih rendah, dengan nilai tertinggi pada Technological Pedagogical Knowledge (81.38) dan terendah pada Technological Pedagogical Content Knowledge (74.31). Hal ini menunjukkan bahwa integrasi ketiga domain tersebut (teknologi, pedagogi, dan konten) memerlukan perhatian lebih untuk meningkatkan pemahaman dan keterampilan. Kesimpulan dari penelitian ini adalah Rata-rata persentase kriteria kualitatif kemampuan TPACK = 81,38 dengan kriteria sangat baik